Galvanic corrosion potential testing method under high-temperature and stress coupling working condition

By processing the material to be tested into an open annular sample and applying stress, combined with electrochemical testing methods, the problem of not being able to monitor the real potential of the material under high temperature and stress coupling conditions is solved, and high-precision galvanic corrosion potential testing is achieved.

CN120161107APending Publication Date: 2025-06-17XIAN RARE METAL MATERIALS RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510375020.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

Under high temperature and stress coupling conditions, the real potential of the material cannot be effectively monitored, making it difficult to grasp the impact of the corrosion system.

Method used

Different stresses are applied by processing the material to be tested into an open annular sample and installing bolts and nuts thereon, adjusting the tightening amount of the nuts to control the downward amount. Then, the working electrode, counter electrode and reference electrode are placed in the heated corrosion solution, and the potential test is performed using an electrochemical workstation to obtain the galvanic corrosion potential under high temperature and stress coupling conditions of the working electrode.

Benefits of technology

The galvanic corrosion potential test is realized under high temperature and stress coupling conditions, and the real potential value changes of the working electrode are monitored. It has simple operation and high test accuracy. It is suitable for corrosion solutions of different materials and different temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120161107A_ABST
    Figure CN120161107A_ABST
Patent Text Reader

Abstract

The invention discloses a galvanic corrosion potential testing method under high temperature and stress coupling conditions. The method comprises the following steps: step 1, calculating parameters; 2, preparing a working electrode; 3, preparing a counter electrode; 4, mounting a high-temperature corrosion device and three electrodes; and 5, carrying out potential test to obtain the galvanic corrosion potential of the working electrode under the working conditions of high temperature and stress coupling. According to the invention, a to-be-tested material A is processed into an open annular sample, a bolt and a nut are mounted on the open annular sample, and the pressing amount is controlled by adjusting the amount of tightening the nut, so that the working electrode under the condition of applying stress is obtained; a working electrode, a counter electrode and a reference electrode are put into a heated corrosion solution and are connected with an electrochemical workstation through wires, potential testing is carried out, the galvanic corrosion potential of the working electrode under the working conditions of high temperature and stress coupling is obtained under the action of an electrochemical disturbance signal, and the real potential numerical value change of the working electrode is monitored.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of measurement of galvanic corrosion potential under high-temperature and stress-coupled working conditions, and particularly relates to a method for measuring galvanic corrosion potential under high-temperature and stress-coupled working conditions. Background Art

[0002] Stress corrosion is mainly a corrosion phenomenon in which a metal material ruptures or even fails under the combined action of stress and a corrosive medium. Galvanic corrosion is a failure form in which two metal materials with a potential difference form a circuit in a corrosive medium to form a primary battery, accelerating the corrosion of the negative electrode material. In fields such as petroleum, chemical industry, and nuclear power, since there are many materials used in the same equipment, the equipment is simultaneously subjected to stress corrosion and galvanic corrosion. Especially in the process of spent fuel reprocessing, such a corrosion system that is coupled for a long time at high temperature will have a certain impact on the true potential of the material. However, in actual working conditions, the true potential of the material cannot be monitored.

[0003] Therefore, it is necessary to provide a method for measuring galvanic corrosion potential under high-temperature and stress-coupled working conditions. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a method for measuring galvanic corrosion potential under high-temperature and stress-coupled working conditions in view of the deficiencies of the above-mentioned prior art. This method controls the downward pressure by adjusting the amount of the tightened nut to obtain a working electrode under the condition of applied stress. By placing the working electrode, counter electrode, and reference electrode into a heated corrosion solution and connecting them to an electrochemical workstation through wires for potential measurement, under the action of an electrochemical perturbation signal, the galvanic corrosion potential of the working electrode under high-temperature and stress-coupled working conditions is obtained, and the change in the true potential value of the working electrode is monitored. The operation is simple and the test accuracy is high.

[0005] To solve the above technical problem, the technical solution adopted by the present invention is: A method for measuring galvanic corrosion potential under high-temperature and stress-coupled working conditions, characterized in that the method includes the following steps: Step 1, calculate parameters: Test the physical parameters of the material A to be measured, and then use the measured physical parameters to calculate the relationship between the deformation amount and the applied stress of the open-ring specimen designed with the material A to be measured, and obtain the downward pressure corresponding to the expected compressive stress; Step 2, prepare the working electrode: Use wire cutting to fabricate the material A to be measured according to the open-ring specimen designed in Step 1 to obtain an open-ring specimen, then process two corresponding round holes on the open-ring specimen, and then pass a bolt through the two round holes and tighten the nut according to the downward pressure obtained in Step 1 to obtain the working electrode; Step 3, prepare the counter electrode: Use wire cutting to fabricate the material B to be measured into a cuboid specimen to obtain the counter electrode; Step 4. Install the high-temperature corrosion device and three electrodes: Connect the working electrode obtained in Step 2, the counter electrode obtained in Step 3, and the reference electrode with wires respectively. Then, place the working electrode, counter electrode, and reference electrode into a container filled with the corrosion solution, and heat the corrosion solution to obtain the high-temperature corrosion device and three electrodes. Step 5. Potential measurement: Connect the wires of the working electrode, counter electrode, and reference electrode in the high-temperature corrosion device and three electrodes obtained in Step 4 to the electrochemical workstation. Then, select the open-circuit potential measurement mode on the electrochemical workstation to perform potential measurement, and obtain the galvanic corrosion potential of the working electrode under the high-temperature and stress coupling conditions.

[0006] Through testing and calculation, the present invention obtains the downward displacement corresponding to different desired compressive stresses of the material A to be tested, realizes various stress conditions. By processing the material A to be tested into the form of an open-ring sample, it is convenient to adjust the diameter of the open-ring sample to apply different stresses, and prevent brittle materials from cracking due to excessive applied stress. By installing bolts and nuts on the open-ring sample and controlling the downward displacement by adjusting the amount of tightened nuts, apply different stresses to the material A to be tested according to the downward displacement of the desired compressive stress, and obtain the working electrode under the applied stress conditions. By placing the working electrode, counter electrode, and reference electrode into the heated corrosion solution and connecting them to the electrochemical workstation with wires, perform potential measurement, and under the action of the electrochemical perturbation signal, obtain the galvanic corrosion potential of the working electrode under the high-temperature and stress coupling conditions.

[0007] In the above method for measuring the galvanic corrosion potential under high-temperature and stress coupling conditions, it is characterized in that the physical parameters in Step 1 include the elastic modulus. By testing the elastic modulus in the present invention, it is convenient to calculate the relationship between the deformation of the open-ring sample made of the material A to be tested and the applied stress.

[0008] In the above method for measuring the galvanic corrosion potential under high-temperature and stress coupling conditions, it is characterized in that the outer diameter of the open-ring sample in Step 1 is 16 mm to 19 mm, the inner diameter is 13 mm to 16 mm, the opening angle is 45° to 60°, and the edge of the open-ring sample is chamfered with a diameter of 0.3 mm to 0.5 mm. By controlling the outer diameter and inner diameter of the open-ring sample in the present invention, it is convenient for the obtained working electrode to have a face ratio immersed in the corrosion solution that meets the actual requirements, and it is also convenient to use the wire cutting method for processing. By controlling the opening angle, the circumferential stress of the open-ring sample meets the requirements, and it is realized that the opposite side of the opening is the maximum stress point, ensuring that the required stress magnitude can be accurately controlled. By chamfering and controlling the chamfering parameters, the generation of stress concentration phenomena during the application of stress is avoided.

[0009] The above-mentioned method for testing the galvanic corrosion potential under high-temperature and stress coupling conditions is characterized in that, in step two, the diameters of the two round holes are both 2 mm to 4 mm, the two round holes are completely opposite to each other, and the connection line of the centers of the two round holes is parallel to the connection line between the open ends. The distances from the centers of the two round holes to the two side edges of the open-ring specimen are both 8 mm to 9.5 mm, and the distances from the centers of the two round holes to the top of the arc of the open-ring specimen are both 18 mm to 22 mm. The present invention facilitates the insertion and extraction of the nut by controlling the diameter of the round hole, and at the same time prevents the influence of too large a diameter on the stress state. By making the two round holes completely opposite to each other and the connection line of the centers of the two round holes parallel to the connection line between the open ends, the centers of the two round holes and the center of the inner diameter of the open-ring specimen are kept on a straight line, which is convenient for the bolt and the nut to cooperate to apply stress to the open-ring specimen, ensuring that the maximum stress point is directly opposite to the open direction when stress is applied. By controlling the distance from the center of the round hole to the edge of the open-ring specimen and the distance from the center of the round hole to the top of the arc of the open-ring specimen, the round hole is located at the central position of the open-ring specimen relative to both sides, ensuring the accuracy of the applied stress.

[0010] The above-mentioned method for testing the galvanic corrosion potential under high-temperature and stress coupling conditions is characterized in that when the downward pressure in step two is positive, the nut is a flat-head nut, and when the downward pressure in step two is negative, the nut is two round-head nuts. The materials of the bolt and the nut in step two are both polyether ether ketone. In the present invention, when the downward pressure is positive, it means that the open-ring specimen needs to be compressed, and the open-ring specimen is compressed by the bolt and the flat-head nut. When the downward pressure is negative, it means that the open-ring specimen needs to be stretched, and the open-ring specimen is stretched by the bolt and the two flat-head nuts arranged up and down inside the open-ring specimen. By controlling the materials of the bolt and the nut, under the condition of facilitating the accurate application of stress, corrosion of the corrosion solution to them is prevented, ensuring the smooth progress of the galvanic corrosion potential test under high-temperature and stress coupling conditions.

[0011] The above-mentioned method for testing the galvanic corrosion potential under high-temperature and stress coupling conditions is characterized in that, in step three, the length of the cuboid specimen is 22 mm to 25 mm, the width is 10 mm to 15 mm, and the height is 2 mm to 5 mm. The present invention controls the size of the cuboid specimen to correspond to the open-ring specimen, meets the requirement of being completely opposite to the maximum stress surface of the open-ring specimen, and functions as a counter electrode.

[0012] The above-mentioned method for testing the galvanic corrosion potential under high-temperature and stress coupling conditions is characterized in that in step four, the joints of the working electrode, the counter electrode and the reference electrode with the wire are all entangled with polytetrafluoroethylene raw tape. By entangling the joints of the working electrode, the counter electrode and the reference electrode with the wire with polytetrafluoroethylene raw tape, the present invention prevents the corrosive solution from corroding the joints, ensuring the accuracy of the galvanic corrosion potential test under high-temperature and stress coupling conditions.

[0013] The above-mentioned method for testing the galvanic corrosion potential under high-temperature and stress coupling conditions is characterized in that in step four, the working electrode and the counter electrode are semi-immersed in the corrosive solution, and the immersed area in the corrosive solution is 30% - 70% of the total area. The working electrode and the counter electrode are kept opposite to each other, the minimum distance between the working electrode and the counter electrode is 10 mm - 100 mm, the reference electrode is immersed below the liquid level of the corrosive solution, and the temperature of the corrosive solution is 95 °C. By controlling the area of the working electrode and the counter electrode semi-immersed in the corrosive solution, the present invention fully restores the real working conditions while meeting the requirements of the face ratio. By keeping the working electrode and the counter electrode opposite to each other, the effect of galvanic corrosion is more directly shown. By controlling the minimum distance between the working electrode and the counter electrode, the electron and ion exchange between the working electrode and the counter electrode in the corrosive solution is faster, quickly realizing the galvanic corrosion effect and improving the test efficiency. By immersing the test part of the reference electrode below the liquid level of the corrosive solution, as the electrode potential reference, the potential change of the working electrode below the liquid level is accurately measured. By controlling the temperature of the corrosive solution, a high-temperature environment is provided.

[0014] The above-mentioned method for testing the galvanic corrosion potential under high-temperature and stress coupling conditions is characterized in that in step four, the corrosive solution is an acid solution, an alkaline solution or a neutral solution. By controlling the composition of the corrosive solution, the present invention realizes the galvanic corrosion potential under high-temperature and stress coupling conditions under different corrosion conditions.

[0015] The above-mentioned method for testing the galvanic corrosion potential under high-temperature and stress coupling conditions is characterized in that in step six, the sampling frequency in the potential test is 5 Hz - 20 Hz, and the test time is 2 h - 8640 h. By controlling the sampling frequency, the present invention ensures that the electrochemical perturbation signal is more stable and the accuracy of the test results is ensured. By controlling the test time, the open-circuit potential of the working electrodes of different materials reaches a stable state, avoiding the phenomenon that the potential has not reached a stable state after the test ends, ensuring the accuracy of the galvanic corrosion potential test under high-temperature and stress coupling conditions.

[0016] The present invention has the following advantages compared with the prior art: 1. The present invention processes the material A to be measured into the form of an open-ring sample, installs bolts and nuts on the open-ring sample, controls the downward pressure by adjusting the amount of tightened nuts, obtains a working electrode under the condition of applied stress, and conducts potential tests by placing the working electrode, counter electrode, and reference electrode into a heated corrosion solution and connecting them to an electrochemical workstation through wires. Under the action of an electrochemical perturbation signal, the galvanic corrosion potential of the working electrode under the coupled working conditions of high temperature and stress is obtained, and the change in the true potential value of the working electrode is monitored. The operation is simple and the test accuracy is high.

[0017] 2. Through testing and finite element calculation, the present invention obtains the downward pressure corresponding to different desired compressive stresses of the material A to be measured, realizes various stress conditions, and by designing the working electrode in the form of an open-ring sample and installing bolts and nuts, precise stress is introduced, eliminating the need for large-scale devices such as universal mechanical testing machines. Moreover, by adjusting the size and downward pressure of the open-ring sample, the purpose of applying different stresses is achieved, and the fracture phenomenon of brittle materials caused by excessive applied stress is prevented. 3. The present invention is applicable to working electrodes prepared from different materials, and can conduct real-time monitoring of the true potential of stress and galvanic coupling corrosion in corrosion solutions at different temperatures, with a wide range of applications.

[0018] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Description of the Drawings

[0019] Figure 1 It is a schematic structural diagram of the open-ring sample of the present invention.

[0020] Figure 2 It is a schematic diagram of the position of the circular hole in the open-ring sample of the present invention.

[0021] Figure 3 It is a schematic diagram of the connection relationship between the open-ring sample of the present invention and the bolt and flat-head nut.

[0022] Figure 4 It is a schematic diagram of the connection relationship between the open-ring sample of the present invention and the bolt and round-head nut.

[0023] Figure 5 It is a schematic diagram of the connection relationship between the working electrode, counter electrode, and reference electrode of the present invention and the electrochemical workstation.

[0024] Figure 6 It is a galvanic corrosion potential curve of the working electrode in Examples 1 - 4 of the present invention under the coupled working conditions of high temperature and stress.

[0025] Description of the Reference Numerals: 1 - Open-ring sample; 2 - Circular hole; 3 - Bolt; 4-1 - Flat-head nut; 4-2 - Round-head nut; 5 - Working electrode; 6—Counter electrode; 7—Reference electrode; 8—Corrosion solution; 9—Container; 10—Heating component; 11—Wire; 12—Electrochemical workstation; 13—Computer. Detailed implementation mode

[0026] Figure 1 is a schematic structural diagram of the open-ring specimen of the present invention, Figure 2 is a schematic diagram of the position of the round hole in the open-ring specimen of the present invention. It can be seen from Figure 1 and Figure 2 that the outer diameter of the open-ring specimen 1 is R1, the inner diameter is R2, the opening angle is θ, the edge of the open-ring specimen 1 is chamfered, two round holes 2 corresponding to each other in position are machined on the open-ring specimen 1, the diameter of the round hole 2 is r, the two round holes 2 are completely opposite to each other, and the connection line of the centers of the two round holes 2 is parallel to the connection line between the open ends. The distances from the centers of the two round holes 2 to the two side edges of the open-ring specimen 1 are d, and the distances from the centers of the two round holes 2 to the top of the arc of the open-ring specimen 1 are L.

[0027] Figure 3 is a schematic diagram of the connection relationship between the open-ring specimen of the present invention and the bolt and flat head nut. It can be seen from Figure 3 that a bolt 3 is inserted through the open-ring specimen 1, and the bolt 3 is fitted with a flat head nut 4-1. By controlling the tightness of the flat head nut 4-1, the downward pressure of the open-ring specimen 1 can be adjusted.

[0028] Figure 4 is a schematic diagram of the connection relationship between the open-ring specimen of the present invention and the bolt and round head nut. It can be seen from Figure 4 that a bolt 3 is inserted through the open-ring specimen 1, and the bolt 3 is fitted with two round head nuts 4-2. The two round head nuts 4-2 are respectively located on the upper and lower sides inside the open-ring specimen 1. The upper round head nut 4-2 and the top of the bolt 3 together clamp the upper part of the open-ring specimen 1. By adjusting the round head nut 4-2 downward, the open-ring specimen 1 can be stretched to achieve a negative downward pressure.

[0029] Figure 5 is a schematic diagram of the connection relationship between the working electrode, counter electrode and reference electrode of the present invention and the electrochemical workstation. It can be seen from Figure 5 that the working electrode 5, counter electrode 6 and reference electrode 7 are placed in a container 9 filled with a corrosion solution 8. A heating component 10 for heating the container 9 and the corrosion solution 8 is arranged at the lower part of the container 9. The working electrode 5, counter electrode 6 and reference electrode 7 are connected to an electrochemical workstation 12 through wires 11, and the electrochemical workstation 12 is connected to a computer 13.

[0030] Example 1 This example includes the following steps: Step 1. Calculate parameters: The elastic modulus of the tested Zr702 alloy is 97100 MPa. The outer diameter of the designed open-ring specimen is 16 mm, the inner diameter is 13 mm, and the opening angle is 45°. Chamfers with a diameter of 0.3 mm are made at the edges of the open-ring specimen. Then, using the elastic modulus, the relationship between the deformation and the applied stress of the designed open-ring Zr702 alloy specimen is calculated by finite element method, and it is obtained that the downward displacement is 0.34 mm when the desired compressive stress is 286 MPa. Step 2. Prepare the working electrode: Use wire cutting to fabricate the Zr702 alloy according to the designed open-ring specimen in Step 1 and polish it with sandpaper to 3000 mesh, then polish it with a polishing liquid with a diameter of 50 nm to obtain an open-ring specimen. Then, process two corresponding round holes on the open-ring specimen. The diameters of both round holes are 2 mm, and the two round holes are completely opposite and parallel to the central axis of the open-ring specimen. The distances from the centers of the two round holes to the two side edges of the open-ring specimen are both 8.0 mm, and the distances from the centers of the two round holes to the top of the arc of the open-ring specimen are both 18 mm. Then, pass a polyetheretherketone bolt through the two round holes and tighten the polyetheretherketone flat nut according to the downward displacement of 0.34 mm obtained in Step 1, so that the vertical outer diameter of the open-ring specimen is 15.66 mm to obtain the working electrode. Step 3. Prepare the counter electrode: Use wire cutting to make a 0Cr 25 Ni 20 stainless steel into a cuboid specimen with a length of 22 mm, a width of 10 mm, and a height of 2 mm to obtain the counter electrode. Step 4. Install the high-temperature corrosion device and the three electrodes: Use wires to connect the working electrode obtained in Step 2, the counter electrode obtained in Step 3, and the reference electrode respectively. The connection parts of the wires are all wrapped with polytetrafluoroethylene raw tape. Then, immerse the working electrode and the counter electrode half in the nitric acid solution with an immersion area of 30% of the total area. The working electrode and the counter electrode are kept opposite, and the minimum distance between the working electrode and the counter electrode is 10 mm. The reference electrode is immersed below the liquid level of the nitric acid solution, and the nitric acid solution is heated to 80 °C to obtain the high-temperature corrosion device and the three electrodes. Step 5. Potential test: Connect the wires of the working electrode, the counter electrode, and the reference electrode in the high-temperature corrosion device and the three electrodes obtained in Step 4 to the electrochemical workstation. Then, select the open-circuit potential test mode on the electrochemical workstation for potential test. The sampling frequency is 5 Hz, and the test time is 2 h to obtain the galvanic corrosion potential of the working electrode under the high-temperature and stress coupling conditions.

[0031] Example 2 This example includes the following steps: Step 1. Calculate parameters: The elastic modulus of the tested Zr702 alloy is 97100 MPa. The outer diameter of the designed open-ring specimen is 19 mm, the inner diameter is 16 mm, and the opening angle is 60°. Chamfers with a diameter of 0.5 mm are made at the edges of the open-ring specimen. Then, using the elastic modulus, the relationship between the deformation and the applied stress of the designed open-ring Zr702 alloy specimen is calculated by finite element method, and the downward displacement is 0.56 mm under the expected compressive stress of 286 MPa. Step 2. Prepare the working electrode: Use wire cutting to fabricate the Zr702 alloy according to the designed open-ring specimen in Step 1 and polish it with sandpaper to 3000 mesh, then polish it with a polishing liquid with a diameter of 50 nm to obtain an open-ring specimen. Then, process two corresponding circular holes on the open-ring specimen. The diameters of the two circular holes are both 4 mm, and the two circular holes are completely opposite and parallel to the central axis of the open-ring specimen. The distances from the centers of the two circular holes to the two side edges of the open-ring specimen are both 9.5 mm, and the distances from the centers of the two circular holes to the top of the arc of the open-ring specimen are both 22 mm. Then, pass a polyether ether ketone bolt through the two circular holes and tighten the polyether ether ketone flat nut according to the downward displacement of 0.56 mm obtained in Step 1, so that the vertical outer diameter of the open-ring specimen is 18.44 mm to obtain the working electrode. Step 3. Prepare the counter electrode: Use wire cutting to make a 0Cr 25 Ni 20 stainless steel into a cuboid specimen with a length of 25 mm, a width of 15 mm, and a height of 5 mm to obtain the counter electrode. Step 4. Install the high-temperature corrosion device and the three electrodes: Connect the working electrode, the counter electrode, and the reference electrode obtained in Step 2 and Step 3 to the wires respectively, and the connections of the wires are wrapped with polytetrafluoroethylene raw tape. Then, immerse the working electrode and the counter electrode half in the hydrochloric acid solution, and the immersion area is 70% of the total area. The working electrode and the counter electrode are kept opposite, and the minimum distance between the working electrode and the counter electrode is 100 mm. The reference electrode is immersed below the liquid level of the hydrochloric acid solution, and the hydrochloric acid solution is heated to 110 °C to obtain the high-temperature corrosion device and the three electrodes. Step 5. Potential test: Connect the wires of the working electrode, the counter electrode, and the reference electrode in the high-temperature corrosion device and the three electrodes obtained in Step 4 to the electrochemical workstation, and then select the open-circuit potential test mode on the electrochemical workstation for potential test. The sampling frequency is 20 Hz, and the test time is 8640 h to obtain the galvanic corrosion potential of the working electrode under the high-temperature and stress coupling conditions.

[0032] Example 3 This example includes the following steps: Step 1. Calculate parameters: Test 0Cr 25 Ni 20The elastic modulus of stainless steel is 194000 MPa. The designed outer diameter of the open-ring specimen is 18 mm, the inner diameter is 15 mm, and the opening angle is 50°. Chamfers with a diameter of 0.4 mm are made at the edges of the open-ring specimen. Then, using the elastic modulus, finite element calculation is carried out for 0Cr 25 Ni 20 The relationship between the deformation amount and the applied stress of the open-ring specimen designed with stainless steel is obtained. When the desired compressive stress is 450 MPa, the downward displacement is 0.39 mm; Step 2. Prepare the working electrode: Use wire cutting to make 0Cr 25 Ni 20 Stainless steel is made according to the open-ring specimen designed in Step 1 and polished with sandpaper to 3000 mesh, and then polished with a polishing liquid with a diameter of 50 nm to obtain an open-ring specimen. Then, two corresponding round holes are machined on the open-ring specimen. The diameters of the two round holes are both 3 mm, and the two round holes are completely opposite and parallel to the central axis of the open-ring specimen. The distances from the centers of the two round holes to the two side edges of the open-ring specimen are both 9.0 mm, and the distances from the centers of the two round holes to the top of the arc of the open-ring specimen are both 20 mm. Then, a polyether ether ketone bolt is passed through the two round holes, and the polyether ether ketone flat head nut is tightened according to the downward displacement of 0.39 mm obtained in Step 1, so that the outer diameter of the open-ring specimen in the vertical direction is 17.61 mm, and the working electrode is obtained; Step 3. Prepare the counter electrode: Use wire cutting to make a cuboid specimen of Zr702 alloy with a length of 23 mm, a width of 12 mm, and a height of 3 mm to obtain the counter electrode; Step 4. Install the high-temperature corrosion device and the three electrodes: The connections between the working electrode, the counter electrode, and the reference electrode obtained in Step 2 and the wires are respectively connected with polytetrafluoroethylene raw tape. Then, the working electrode and the counter electrode are semi-immersed in the sodium hydroxide solution, and the immersed area is 50% of the total area. The working electrode and the counter electrode are kept opposite, and the minimum distance between the working electrode and the counter electrode is 50 mm. The reference electrode is immersed below the liquid level of the sodium hydroxide solution, and the sodium hydroxide solution is heated to 95 °C to obtain the high-temperature corrosion device and the three electrodes; Step 5. Potential test: Connect the wires of the working electrode, the counter electrode, and the reference electrode in the high-temperature corrosion device and the three electrodes obtained in Step 4 to the electrochemical workstation. Then, select the open-circuit potential test mode on the electrochemical workstation for potential testing. The sampling frequency is 10 Hz, and the testing time is 5 h to obtain the galvanic corrosion potential of the working electrode under the high-temperature and stress coupling conditions.

[0033] Example 4 This example includes the following steps: Step 1. Calculate parameters: Test 0Cr 25Ni 20 The elastic modulus of stainless steel is 194000 MPa. The outer diameter of the designed open-ring specimen is 18 mm, the inner diameter is 15 mm, and the opening angle is 50°. Chamfers with a diameter of 0.4 mm are made at the edges of the open-ring specimen, and then the deformation of the open-ring specimen designed with 0Cr 25 Ni 20 The relationship between the deformation of the open-ring specimen designed with stainless steel and the applied stress is obtained. When the desired compressive stress is 450 MPa, the downward displacement is -0.39 mm; Step 2. Prepare the working electrode: Use wire cutting to fabricate 0Cr 25 Ni 20 Stainless steel according to the open-ring specimen designed in Step 1, and polish it with sandpaper to 3000 mesh, then polish it with a polishing solution with a diameter of 50 nm to obtain an open-ring specimen. Then, process two corresponding round holes on the open-ring specimen. The diameters of the two round holes are both 3 mm, and the two round holes are completely opposite and parallel to the central axis of the open-ring specimen. The distances from the centers of the two round holes to the two side edges of the open-ring specimen are both 9.0 mm, and the distances from the centers of the two round holes to the top of the arc of the open-ring specimen are both 20 mm. Then, pass a polyether ether ketone bolt through the two round holes and tighten the two polyether ether ketone round nuts according to the downward displacement of -0.39 mm obtained in Step 1, so that the vertical outer diameter of the open-ring specimen is 18.39 mm to obtain the working electrode; Step 3. Prepare the counter electrode: Use wire cutting to fabricate a cuboid specimen made of Zr702 alloy with a length of 23 mm, a width of 12 mm, and a height of 3 mm to obtain the counter electrode; Step 4. Install the high-temperature corrosion device and the three electrodes: Connect the working electrode obtained in Step 2, the counter electrode obtained in Step 3, and the reference electrode to the wires respectively. The connection points of the wires are all wrapped with polytetrafluoroethylene raw tape. Then, immerse the working electrode and the counter electrode half in the simulated feed liquid, and the immersion area is 50% of the total area. The working electrode and the counter electrode are kept opposite, and the minimum distance between the working electrode and the counter electrode is 50 mm. The reference electrode is immersed below the liquid level of the sodium chloride solution, and heat the simulated feed liquid to 95 °C to obtain the high-temperature corrosion device and the three electrodes; Step 5. Potential measurement: Connect the wires of the working electrode, the counter electrode, and the reference electrode in the high-temperature corrosion device and the three electrodes obtained in Step 4 to the electrochemical workstation. Then, select the open-circuit potential measurement mode on the electrochemical workstation to measure the potential. The sampling frequency is 10 Hz, and the measurement time is 5 h to obtain the galvanic corrosion potential of the working electrode under the high-temperature and stress coupling conditions.

[0034] Figure 6 The galvanic corrosion potential curves of the working electrodes in Examples 1 to 4 of the present invention under the high-temperature and stress coupling conditions are shown. FromFigure 6 It can be seen that the galvanic corrosion potential curves in Examples 1 to 4 are true and effective, that is, the true potential of the working electrode is monitored in real time. The final stable potential of Example 1 is 0.947V, the final stable potential of Example 2 is 0.991V, the final stable potential of Example 3 is 0.933V, and the final stable potential of Example 4 is 0.887V.

[0035] The above are only the preferred embodiments of the present invention and do not impose any limitations on the present invention. Any simple modifications, changes, and equivalent variations made to the above embodiments based on the technical essence of the present invention still fall within the protection scope of the technical solution of the present invention.

Claims

1. A method for testing galvanic corrosion potential under high temperature and stress coupling conditions, characterized in that: The method comprises the following steps: Step 1, calculating parameters: testing the physical parameters of the material A to be tested, and then using the tested physical parameters to calculate the relationship between the deformation and applied stress of the open ring specimen designed with the material A to be tested, and obtaining the downward pressure corresponding to the expected compressive stress; Step 2, preparing a working electrode: using a wire cutting method to make the material A to be tested according to the open ring sample designed in step 1 to obtain an open ring sample, and then processing two circular holes corresponding to the positions on the open ring sample, and then passing the bolt through the two circular holes, and tightening the nut according to the downward pressure obtained in step 1, to obtain a working electrode; Step 3: Prepare the counter electrode: Use the wire cutting method to make the material B to be tested into a rectangular parallelepiped sample to obtain the counter electrode; Step 4: Install the high-temperature corrosion device and three electrodes: Use wires to connect the working electrode obtained in step 2, the counter electrode obtained in step 3, and the reference electrode, and then put the working electrode, the counter electrode, and the reference electrode into a container filled with a corrosion solution, and heat the corrosion solution to obtain a high-temperature corrosion device and three electrodes; Step 5. Potential test: Connect the high-temperature corrosion device obtained in step 4 and the wires of the working electrode, counter electrode and reference electrode in the three electrodes to the electrochemical workstation, and then select the open circuit potential test mode on the electrochemical workstation to perform a potential test to obtain the galvanic corrosion potential of the working electrode under high temperature and stress coupling conditions.

2. The galvanic corrosion potential testing method under high temperature and stress coupling conditions according to claim 1 is characterized in that: The physical parameters in step 1 include elastic modulus.

3. The galvanic corrosion potential testing method under high temperature and stress coupling conditions according to claim 1 is characterized in that: The outer diameter of the open ring sample in step 1 is 16 mm to 19 mm, the inner diameter is 13 mm to 16 mm, the opening angle is 45° to 60°, and the edge of the open ring sample is chamfered with a diameter of 0.3 mm to 0.5 mm.

4. The method for testing galvanic corrosion potential under high temperature and stress coupling conditions according to claim 1, characterized in that: In step 2, the diameters of the two circular holes are both 2mm~4mm, the two circular holes remain completely opposite, and the line connecting the centers of the two circular holes is parallel to the line connecting the open ends, the distances from the centers of the two circular holes to the edges of both sides of the open ring sample are both 8mm~9.5mm, and the distances from the centers of the two circular holes to the top of the arc of the open ring sample are both 18mm~22mm.

5. The method for testing galvanic corrosion potential under high temperature and stress coupling conditions according to claim 1, characterized in that: When the downward pressure in step 2 is a positive value, the nut is a flat-head nut; when the downward pressure in step 2 is a negative value, the nut is two round-head nuts; and the material of the bolt and nut in step 2 is polyetheretherketone.

6. The method for testing galvanic corrosion potential under high temperature and stress coupling conditions according to claim 1, characterized in that: The rectangular parallelepiped sample described in step 3 has a length of 22 mm to 25 mm, a width of 10 mm to 15 mm, and a height of 2 mm to 5 mm.

7. The method for testing galvanic corrosion potential under high temperature and stress coupling conditions according to claim 1, characterized in that: In step 4, the connections between the working electrode, the counter electrode, the reference electrode and the wire are all entangled with polytetrafluoroethylene raw tape.

8. The method for testing galvanic corrosion potential under high temperature and stress coupling conditions according to claim 1, characterized in that: In step 4, the working electrode and the counter electrode are half immersed in the corrosion solution, and the area immersed in the corrosion solution is 30% to 70% of the total area. The working electrode and the counter electrode remain opposite to each other, that is, the open side of the working electrode is facing away from the counter electrode, and the side with the largest surface area of ​​the counter electrode faces the working electrode. The minimum distance between the working electrode and the counter electrode is 10 mm to 100 mm. The reference electrode is immersed below the liquid surface of the corrosion solution, and the temperature of the corrosion solution is 80°C to 110°C.

9. The method for testing galvanic corrosion potential under high temperature and stress coupling conditions according to claim 1, characterized in that: The corrosive solution in step 4 is an acid solution, an alkaline solution or a neutral solution.

10. The method for testing galvanic corrosion potential under high temperature and stress coupling conditions according to claim 1, characterized in that: The sampling frequency in the potential test described in step 6 is 5 Hz to 20 Hz, and the test time is 2 h to 8640 h.